Do the weeding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Proceedings of the 17th Biennial Weed Science Society Conference for Eastern Africa, held in Harare, Zimbabwe in September 1999. Edited by OA Chivinge, G Tusiime, P Nampala and E Adipala, WSSEA, with support of CTA, as a special edition of the African Cro